2016
DOI: 10.1007/s11665-016-2151-z
|View full text |Cite
|
Sign up to set email alerts
|

Weathering and Biodegradation Study on Graft Copolymer Compatibilized Hybrid Bionanocomposites of Poly(Lactic Acid)

Abstract: This work reports on the influence of moisture absorption and accelerated weathering on the properties of graft copolymer compatibilized bionanocomposites of poly(lactic acid) (PLA). Moisture absorption tests were conducted for 30 days by immersing the samples in a distilled water bath at room temperature, and the amount of moisture absorbed in each time interval was measured. The rate of moisture uptake decreased by incorporation of C30B nanoclay and graft copolymer into fiber-reinforced PLA composites. Chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Although the coupling agent showed to be effective in the flexural and tensile properties for agave biocomposites (at weathering time 0), the humidity of weathering conditions causes water absorption of the fibers inducing the fibermatrix debonding. 39 The less compatibility achieved in coir biocomposites (at weathering time 0) resulted in materials in which fiber debonding by weathering becomes easier, and consequently, a lower tensile load was supported. Contrary to the tensile strength, where good compatibility is essential to avoid fiber debonding, the results of flexural properties showed that weathering conditions cause lower damage to coir fibers biocomposites by their higher lignin content that reduce fibers swelling.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Although the coupling agent showed to be effective in the flexural and tensile properties for agave biocomposites (at weathering time 0), the humidity of weathering conditions causes water absorption of the fibers inducing the fibermatrix debonding. 39 The less compatibility achieved in coir biocomposites (at weathering time 0) resulted in materials in which fiber debonding by weathering becomes easier, and consequently, a lower tensile load was supported. Contrary to the tensile strength, where good compatibility is essential to avoid fiber debonding, the results of flexural properties showed that weathering conditions cause lower damage to coir fibers biocomposites by their higher lignin content that reduce fibers swelling.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The main degradation products are carboxylic end groups, ketones, hydroperoxides, and hydroxyl products. Additionally, the addition of nano clays results in the formation of an intricate labyrinthine network that slows down the diffusion of water, leading to increased resistance to accelerated weathering [ 55 ].…”
Section: Case Studies On Weatheringmentioning
confidence: 99%
“…It was determined that amorphous and crystalline PLA lament specimens in humid environments at various temperatures showed signi cant moisture absorption and allow hydrolysis to occur [9]. Exposure to moisture causes signi cant reductions in the mechanical properties of PLA lament and leads to a change in other properties such as surface roughness [10][11][12]. The degree of crystallinity of PLA laments that have been dehumidi ed or exposed to water increases.…”
Section: Introductionmentioning
confidence: 99%